Auditoría operativa y su incidencia en los procesos contables financieros de la compañía de transportes ramehi s.a transramehi, cantón Valencia año 2017 - 2018. - Pinto Arboleda, Rafael Antonio (2019)
This research work aims to determine the impact of the operational audit on the financial accounting processes of the Company of Transport RAMEHI S.A. TRANSRAMEHI, an examination that will reveal whether the company operates in an analytical, objective and systematic way, to determine if acceptable policies and procedures are carried out, if the established norms are followed and if the resources are used effectively and efficiently. The company presents difficulties in the application of procedures as it does not have an accounting policy manual, which affects the presentation of financial information affecting the decision making by the Management, however there is a compliance with the rules but not in its entirety, there is no manual of functions which does not prevent the staff from fulfilling their activities, the flow of information exists due to the needs of the company, but not because a structural organization chart requires it, there is no evaluation before the existence of risks. The investigative process has as specific objectives to examine the accounting procedures of the Transport Company RAMEHI SA TRANSRAMEHI, according to the requirements of the laws, regulations and standards, assess the level of confidence of internal control in the accounting and financial processes through COSO I and verify the level of effectiveness presented by the accounting and financial information, which, through methods, techniques and a series of audit procedures were met, provided results in which it was determined that there is a compliance with the laws, its regulations and norms that govern The financial accounting processes, additional controls are not met efficiently although the risk is 22% considered as low - medium and finally the control procedures regarding the efficiency of financial accounting information are not optimal, although there is liquidity in the company, so it is then concluded and recommended with base to the results obtained from the investigation. Keywords: Operational audit, COSO I, financial accounting process.